CO2-induced destabilization of pyrite-structured FeO2Hx in the lower mantle. Issue 6 (15th March 2018) - Boulard, Eglantine; Guyot, François; Menguy, Nicolas; Corgne, Alexandre; Auzende, Anne-Line; Perrillat, Jean-Philippe; Fiquet, Guillaume
Abstract: Volatiles, such as carbon and water, modulate the Earth's mantle rheology, partial melting and redox state, thereby playing a crucial role in the Earth's internal dynamics. We experimentally show the transformation of goethite FeOOH in the presence of CO2 into a tetrahedral carbonate phase, Fe4 C3 O12, at conditions above 107 GPa—2300 K. At temperatures below 2300 K, no interactions are evidenced between goethite and CO2, and instead a pyrite-structured FeO2 Hx is formed as recently reported by Hu et al. (2016; 2017) and Nishi et al. (2017). The interpretation is that, above a critical temperature, FeO2 Hx reacts with CO2 and H2, yielding Fe4 C3 O12 and H2 O. Our findings provide strong support for the stability of carbon-oxygen-bearing phases at lower-mantle conditions. In both subducting slabs and lower-mantle lithologies, the tetrahedral carbonate Fe4 C3 O12 would replace the pyrite-structured FeO2 Hx through carbonation of these phases. This reaction provides a new mechanism for hydrogen release as H2 O within the deep lower mantle. Our study shows that the deep carbon and hydrogen cycles may be more complex than previously thought, as they strongly depend on the control exerted by local mineralogical and chemical environments on the CO2 and H2 thermodynamic activities.